A southern African perspective on the co-evolution of early life and environments - (:unkn) unknown (My University, 2021)
Abstract The Kaapvaal and Zimbabwe cratons host some of the earliest evidence for life. When compared to the contemporaneous East Pilbara craton, cherts and other metasedimentary horizons in southern Africa preserve traces of life with far greater morphological and geochemical fidelity. In spite of this, most fossiliferous horizons of southern Africa have received relatively limited attention. This review summarises current knowledge regarding the nature of early life and its distribution with respect to environments and ecosystems in the Archaean (>2.5 Ga) of the region, correlating stratigraphic, sedimentological, geochemical and palaeontological understanding. There is abundant and compelling evidence for both anoxygenic photosynthetic and chemosynthetic biomes dominating Palaeoarchaean-Mesoarchaean strata dating back to around 3.5 Ga, and the prevalence of each is tied to palaeoenvironmental parameters deducible from the rock record. Well-developed, large stromatolites characteristic of younger Mesoarchaean-Neoarchaean sequences were probably constructed by oxygenic photosynthesisers. Isotopic evidence from the Belingwe greenstone belt and the Transvaal Supergroup indicates that both a full sulphur cycle and complex nitrogen cycling were in operation by the Mesoarchaean-Neoarchaean. The Archaean geological record of southern Africa is thus a rich repository of information regarding the co-evolving geosphere and biosphere in deep time.
Keywords: African Research